Time, talent, energy overcome organizational drag and unleash your team's productive power - Mankins, Michael C. (Ascent Audio, 2024)
Business leaders know that the key to competitive success is smart management of scarce resources. That's why companies allocate their financial capital so carefully. But capital today is cheap and abundant, no longer a source of advantage. The truly scarce resources now are the time, the talent, and the energy of the people in your organization-resources that are too often squandered. Building off of the popular Harvard Business Review article "Your Scarcest Resource," Michael Mankins and Eric Garton, Bain & Company experts in organizational design and effectiveness, present new research into how you can liberate people's time, talent, and energy and unleash your organization's productive power. They identify the specific causes of organizational drag-the collection of institutional factors that slow things down, decrease output, and drain people's energy-and then offer a pragmatic framework for how managers can overcome it. With practical advice for using the framework and in-depth examples of how the best companies manage their people's time, talent, and energy with as much discipline as they do their financial capital, this book shows managers how to create a virtuous circle of high performance.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Organizational effectiveness; Management; Corporate culture; Personnel management; Efficacité organisationnelle; Gestion; Personnel; Direction; management; Audiobooks; Livres audio